2016
DOI: 10.5935/1678-9741.20160024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LIMA Harvesting Technique on Postoperative Drainage in Off-Pump CABG

Abstract: ObjectiveWe investigated the effects of pedicled and semiskeletonized left internal mammary artery (LIMA) harvesting techniques on postoperative drainage in patients subjected to off-pump CABG, ignoring other advantages or disadvantages of those techniques.MethodsThe present study comprises a total of 160 subjects that underwent coronary artery bypass surgery in our clinic. Data were collected consecutively and retrospectively. An attempt was made to have similar groups in terms of demographic characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In a study by Ozulku and Aygun on 160 subjects underwent CABG, they found that the amount of drainage was higher in the pedicled group [21]. In our study, there were 16 patients who developed wound infection; two patients underwent sternal rewiring.…”
Section: Discussionsupporting
confidence: 42%
“…In a study by Ozulku and Aygun on 160 subjects underwent CABG, they found that the amount of drainage was higher in the pedicled group [21]. In our study, there were 16 patients who developed wound infection; two patients underwent sternal rewiring.…”
Section: Discussionsupporting
confidence: 42%
“…LITA is the most commonly used arterial graft in CABG accounting for its satisfactory patency rate, convenience for coronary artery anastomosis when it does not need proximal anastomosis. The importance of LITA graft use was emphasized in numerous reports, and the LITA graft use had proven to decrease the mortality rates and increase long-term survival in both male and female CABG patients [ 30 - 32 ] . Therefore, LITA as coronary bypass graft in our practice is commonly preferred.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for poor and inconsistent LIMA blood flow after topical application of papaverine alone in pedicled LIMA (1–1.5 cm) is the presence of thick tissue comprised of an intrathoracic fascia, adipose tissue, and muscle around the LIMA preventing the adequate contact of the conduit with the vasodilator. [ 16 ] Several investigators, Mulay et al . [ 17 ] and Girard et al .…”
Section: Discussionmentioning
confidence: 99%